The optimal warming strategy to reduce perioperative hypothermia: A prospective randomized non-blinded clinical trial. - Ronak Desai; Jason Gosschalk; Noud van Helmond; Ludmil Mitrev; Catherine Zhang; Brian McEniry; Krystal Hunter; Ernest Wallace; Michele Mele; Jennifer Ocbo; Keyur Trivedi; George Hsu; et al. (PLoS ONE)
Background To mitigate perioperative hypothermia, patients can be warmed preoperatively and intraoperatively with forced-air warming (FAW) and conductive warming (CW) methods. We examined the association of four combinations of pre- and intraoperative CW and FAW with the magnitude of intraoperative hypothermia. Methods We conducted a prospective randomized trial at a tertiary healthcare center in the United States (trial registration number ISRCTN23065394). Patients were randomized to 4 arms based on the following pre/intraoperative warming combinations: (1) CW/CW, (2) FAW/FAW, (3) no active prewarming (NAPW)/CW, (4) NAPW/FAW. Body temperature was measured using an esophageal probe. The area under the temperature curve (AUC) below 36°C was calculated according to the trapezoidal rule and quantified intraoperative hypothermia. A mixed model was used to estimate differences in AUC between the 4 arms. Results 182 patients were analyzed. Patients in the NAPW/FAW arm had the highest AUC values while those in the CW/CW arm had the lowest. AUC values [median (Q1, Q3] were as follows: CW/CW = 4.7 (0, 26.6); FAW/FAW = 8.0 (0, 30.8); NAPW/CW = 7.4 (0, 27.1); NAPW/FAW = 19.9 (5.0, 44.3). Mixed model results showed significant lower AUC values in CW/CW and NAPW/CW when compared to NAPW/FAW. The ratio of mean AUC [95% CI] between CW/CW vs NAPW/FAW was 0.49 [0.24, 0.98], 51% lower, and between NAPW/CW and NAPW/FAW, 0.46 [0.23, 0.91], 54% lower. When the AUC was normalized to the duration of surgery (AUC/case duration in°C, or "relative AUC"), significant lower relative AUC values were observed between FAW/FAW vs NAPW/FAW (48% lower, p = 0.0419) and NAPW/CW vs NAPW/FAW (48% lower, p = 0.0407). Conclusions CW is more effective than FAW at reducing intraoperative hypothermia when FAW is used without prewarming. When patients are actively prewarmed, CW and FAW show no difference in their ability to maintain patient temperature.